2018
DOI: 10.1093/jnci/djy099
|View full text |Cite
|
Sign up to set email alerts
|

Novel Common Genetic Susceptibility Loci for Colorectal Cancer

Abstract: This study provides insight into the architecture of common genetic variation contributing to CRC etiology and improves risk prediction for individualized screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
153
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 144 publications
(163 citation statements)
references
References 36 publications
(33 reference statements)
4
153
0
Order By: Relevance
“…5 Polygenic risk scores derived from these studies have evaluated that some 5% of the study populations have over twofold increased risk of CRC. 32,33 In our study also, we observed an increased risk for individuals with increasing number of alleles causing a moderately increased CRC risk. However, polygenic risk scores do not take into account epistatic interactions, which may by far cause a more pronounced risk compared to single variants, as shown in our study.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…5 Polygenic risk scores derived from these studies have evaluated that some 5% of the study populations have over twofold increased risk of CRC. 32,33 In our study also, we observed an increased risk for individuals with increasing number of alleles causing a moderately increased CRC risk. However, polygenic risk scores do not take into account epistatic interactions, which may by far cause a more pronounced risk compared to single variants, as shown in our study.…”
Section: Discussionsupporting
confidence: 79%
“…So far, about 100 CRC susceptibility loci have been identified through genome‐wide association studies . Polygenic risk scores derived from these studies have evaluated that some 5% of the study populations have over twofold increased risk of CRC . In our study also, we observed an increased risk for individuals with increasing number of alleles causing a moderately increased CRC risk.…”
Section: Discussionsupporting
confidence: 65%
“…Traditional approaches of calculating the explained proportion of familial risk by common genetic variants have been widely employed in the GWAS literature . Manuscripts reporting on the newly identified susceptibility loci commonly estimate the incremental and total proportion of familial risk explained by the respective SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Manuscripts reporting on the newly identified susceptibility loci commonly estimate the incremental and total proportion of familial risk explained by the respective SNPs. For example, so far published estimates for the familial risk for CRC allegedly explained by common genetic variants ranged from ~6% for 10 SNPs, to ~8% for 20 SNPs under observation, to ~12% for 76 SNPs, to ~22% for 45 SNPs in a simulation study. Most studies took some LD measure into account, while others simply added up contributions of SNPs without LD‐pruning .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation